STRATEGI PEMASARAN INOVATIF DALAM MENARIK GENERASI Z SEBAGAI NASABAH BANK SYARIAH - Iviola Sabila Avandi; Muhammad Iqbal Fasa; Is Susanto (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This study aims to examine innovative marketing strategies that can be applied by Islamic banks to attract Generation Z as customers. Generation Z, born between 1995 and 2010, has unique characteristics with a strong tendency towards digital technologies and online-based services. This article highlights the importance of digitizing Islamic banking services through user-friendly mobile applications and social media, as well as the importance of marketing strategies through collaboration with influencers. In addition, research shows that Generation Z has a preference for ethical and transparent banking services, in line with Sharia principles. Literature studies, statistical data, and qualitative analysis are used to understand the behavior and needs of Generation Z in the context of Islamic bank Marketing. In conclusion, innovative marketing strategies that utilize digital technology, personalized services, and interactive campaigns on social media are essential in attracting Generation Z and increasing the competitiveness of Islamic banks in the digital age.